2003
DOI: 10.3177/jnsv.49.422
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Suggesting That Difructose Anhydride III Is an Indigestible and Low Fermentable Sugar during the Early Stages after Ingestion in Humans

Abstract: We investigated the influences of difructose anhydride III (DFAIII), a novel commercially available disaccharide, on sugar metabolism, breath hydrogen and serum ace tate in the early stages after ingestion to determine whether DFAIII is an indigestible sugar and to what degree it is fermentable in humans. This study was designed as a randomized controlled single-blind crossover test with 9 healthy subjects, who drink a 200mL water solution containing 10g of DFAIII, lactulose or sucrose following overnight fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…observe a slightly higher level of breath hydrogen at h 8 in the post-DFAIII DL test as compared to the values for the pre-ingestion DL test. These higher levels of breath hydrogen observed in the post-DFAIII ingestion DL test, however, were much lower than the breath hydrogen levels of above 25 and 60 ppm seen after respectively ingestiing of 10 g of lactulose 14) and FOS. 20) These results indicate that DFAIII can still be classified as low fermentable until h 9 after a 12-day feeding period of DFAIII, and that repeated ingestion of DFAIII does not promote fermentability during the period.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…observe a slightly higher level of breath hydrogen at h 8 in the post-DFAIII DL test as compared to the values for the pre-ingestion DL test. These higher levels of breath hydrogen observed in the post-DFAIII ingestion DL test, however, were much lower than the breath hydrogen levels of above 25 and 60 ppm seen after respectively ingestiing of 10 g of lactulose 14) and FOS. 20) These results indicate that DFAIII can still be classified as low fermentable until h 9 after a 12-day feeding period of DFAIII, and that repeated ingestion of DFAIII does not promote fermentability during the period.…”
Section: Discussionmentioning
confidence: 68%
“…The supernatant were then analyzed as previously reported. 14) Breath samples were collected in bags designed to obtain the alveolar air (GaSampler Ò ; Quintron, Milwaukee, USA) and analyzed by gas chromatography (Microlyzer DP; Quintron) on the same day.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The evertedsac and Ussing-chamber techniques have shown that indigestible disaccharides (e.g., maltitol and difructose anhydride (DFA)) directly increase the intestinal permeability of Ca in the absence of fermentation (21)(22)(23). This increase depends on the types of indigestible saccharides used in the Ussing-chamber technique (22,24).…”
Section: Discussionmentioning
confidence: 99%